From Qalam to Quantum: The Evolution of Arabic Learning in the Era of Artificial Intelligence - Sari, Rizka; Angkara, Randi Redam (Proceeding of International Conference on Islamic Education (ICIED), 2025)
The rapid advancement of Artificial Intelligence (AI) is reshaping global educational paradigms, including the teaching and learning of Arabic as a language of faith, knowledge, and civilization. This study examines the epistemological shift from Qalam a classical symbol of knowledge in the Islamic tradition to Quantum, representing the digital and intelligent era of education. Using a qualitative descriptive approach, the paper analyzes the transformation of Arabic pedagogy from traditional kitabiyah learning to AI-driven environments such as adaptive learning platforms, intelligent tutoring systems, and generative chatbots. The findings reveal a dual challenge: integrating AI innovations while preserving the spiritual and cultural essence of Arabic education. Results indicate that AI enhances linguistic competence and learner engagement, yet demands new frameworks such as Tarbiyah Quantum, a synthesis of spiritual and artificial intelligence. The study concludes by proposing a holistic pedagogical model that humanizes AI in Arabic learning, ensuring technology serves as a support rather than a replacement for rūḥ al-tarbiyah.